Fostering Sustainable Tourism Innovation through Agro-Eco-Edu-Tourism: A Teaching Factory (TeFa) Collaboration Between Vocational Schools and Destination Managers in Batu City - Fiki Yusufi Afrian Suhansa; Moh Khusaini; Fitri Candra Wardana (STAI Hubbulwathan Duri, 2025)
This study examines the implementation of the Agro-Eco-Edu-Tourism Program in the Teaching Factory (TeFa) model, a collaborative effort between vocational high schools and tourism destination managers in Batu City, aimed at integrating sustainability into tourism education and practice. A qualitative multi-site case study design was employed, collecting data through interviews, observations, and documentation from a public and a private vocational high school, both offering hospitality and tourism programs. Informants included school principals, teachers, students, and tourism managers. Findings indicate that the program successfully integrates eco-friendly practices into tourism operations through organic farming, eco-guided tours, the use of local products in hospitality services, and renewable energy adoption. These initiatives have enhanced tourism destinations by attracting eco-conscious visitors and promoting regional sustainability. For students, the program provided practical skills, real-world industry exposure, increased employability, and expanded professional networks. The results highlight the potential of school-industry collaboration to foster innovation in sustainable tourism education. Key challenges identified include the need for better coordination among stakeholders, deeper community involvement, and the integration of advanced eco-tourism technologies. The Agro-Eco-Edu-Tourism Program demonstrates an effective model for merging educational outcomes with sustainable tourism development. Strengthening stakeholder collaboration and securing long-term funding are recommended to enhance program sustainability.